Antonio Machado, el largo peregrinar hacia la mar - Alonso, Monique; Tello, Antonio, 1945-; Guerra, Alfonso, 1940- (Barcelona : Octaedro, 2014)
About the last years of Machado's life.
Online resource; title from PDF title page (Digitalia, viewed January 13, 2017)
Keywords: Machado, Antonio, -- 1875-1939 -- Last years; Machado, Antonio, -- 1875-1939 -- Exile -- France; Authors, Spanish -- 20th century -- Biography; Electronic books